2024
DOI: 10.3847/1538-4357/ad187d
|View full text |Cite
|
Sign up to set email alerts
|

Properties of an Interplanetary Shock Observed at 0.07 and 0.7 au by Parker Solar Probe and Solar Orbiter

Domenico Trotta,
Andrea Larosa,
Georgios Nicolaou
et al.

Abstract: The Parker Solar Probe (PSP) and Solar Orbiter (SolO) missions opened a new observational window in the inner heliosphere, which is finally accessible to direct measurements. On 2022 September 5, a coronal mass ejection (CME)-driven interplanetary (IP) shock was observed as close as 0.07 au by PSP. The CME then reached SolO, which was radially well-aligned at 0.7 au, thus providing us with the opportunity to study the shock properties at different heliocentric distances. We characterize the shock, investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…Although the dispersion shape of the onset of the SEPs is well explained by a diffusive shock acceleration process, it is less clear what leads to the intensity drop at the shock. Trotta et al (2024) analyzed the characteristics of the shock observed at Parker and compared them to those of the shock observed significantly later by SolO, at 0.7 au. As can be seen from Figure 1, SolO was roughly radially aligned with Parker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the dispersion shape of the onset of the SEPs is well explained by a diffusive shock acceleration process, it is less clear what leads to the intensity drop at the shock. Trotta et al (2024) analyzed the characteristics of the shock observed at Parker and compared them to those of the shock observed significantly later by SolO, at 0.7 au. As can be seen from Figure 1, SolO was roughly radially aligned with Parker.…”
Section: Discussionmentioning
confidence: 99%
“…If so, this may be relevant to unexpected changes in the energetic proton intensities at the shock passage.The sheath region as identified byRomeo et al (2023) is quite short, lasting only 5 minutes between the shock passage and a small rotation of the magnetic field theta angle (seeRomeo et al 2023, their Figure2). The entry into the CME flank is marked by the depressed proton kinetic temperature, starting 29 minutes after the end of the sheath Trotta et al (2024),. however, state that the boundary between the sheath and the start of the flux rope is not very clear.…”
mentioning
confidence: 99%